Performance Evaluation of Articulated Bus as a Mode of Public Transport of Dhaka: A Case Study of Gazipur to Gabtoli Route - Satu, Shammi Akter; Shakil, Hedayet Islam (Journal of Bangladesh Institute of Planners, 2017)
Dhaka, as a city of a developing country, is struggling to improve and enhance existing transit services at a low cost. The Articulated Bus Service is a newly introduced public transport mode in the transportation system of Dhaka city. Although a total of only 25 articulated buses operate from Gazipur and Gabtoli route, it is important to assess the role of the articulated bus services in order to justify the continuation of such services as well as considering the possible expansion to meet the popular demand for such services. The paper aims to evaluate the quality of service provision and examine the overall prospect of the articulated bus service in Dhaka. A passengers’ attitude survey was carried out about the overall performance of BRTC’s articulated bus and privately operated single decker bus services. Several service performance indicators were used to measure the performance and quality of these two bus modes considering the users’ point of view. It was revealed that overall performance of articulated buses was better than single decker bus services. The Articulated Bus Service shows huge potential in enhancing the transportation condition of Dhaka city through contribution to reducing congestion, environmental pollution, unreliability, delay and providing better services at reasonable fares. JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 41-54